Toughening poly(l-lactide) blends: effectiveness of sequence-controlled six-arm star-branched block copolymers of poly(L-lactide) and poly(epsilon-caprolactone) - Deokar, Megha D.; Garnaik, Baijayantimala; Sivaram, Swaminathan (ACS Omega, 2022)
Well-defined six-arm star-branched bio-degradable block copolymers of L-lactide and epsilon-caprolactone were prepared using controlled ring-opening polymerization and a sequential monomer addition method using dipentaerythritol as the initiator core and organocatalysts at low temperatures in solution. Sequence of enchainment was changed by reversing the order of monomer addition giving, either, a crystalline PLA block or an amorphous PCL block as the outer segment. Well-defined six-arm poly(epsilon-caprolactone-b-L-lactide, 6s-PCL-b-PLA) block copolymers were obtained with a range of segment molecular weights. However, in the case of six-arm poly(L-lactide-b-epsilon-caprolactone, 6s-PLA-b-PCL), disruption of the block structure was observed on account of competing transesterification reactions accompanying a chain-growth reaction. Such sequence-controlled block copolymers showed interesting phase morphologies, as evidenced by differential scanning calorimetry (DSC) studies. 6s-PCL-b-PLA showed two glass-transition temperatures and two melting temperatures characteristic of the amorphous and crystalline blocks. 6s-PCL-b-PLA and 6s-PLA-b-PCL with different segment chain lengths were solution blended (10 wt %) with a commercially sourced PLA. All the blends were highly transparent. The structure and properties of the blend were examined by DSC, measurement of mechanical properties, and scanning electron microscopy. The results show that a phase-separated 6s-PCL-b-PLA copolymer results in two- to three-fold improvement in tensile toughness without the loss of modulus. A possible hypothesis for the mechanism of tensile toughness in the blend has been proposed.